Motion - Colonoscopic Surveillance is more Cost Effective than Colectomy in Patients with Ulcerative Colitis: Arguments Against the Motion - Anders Ekbom (Canadian Journal of Gastroenterology)
There are insufficient data upon which to base recommendations about surveillance colonoscopy and prophylactic colectomy for the prevention of colorectal cancer in patients with ulcerative colitis. Case series, analyses of intermediate results and extrapolations from other patient groups do not constitute reliable evidence. Available studies are susceptible to several biases: the ’healthy worker’ effect, surveillance bias and selection bias. Patients who are enrolled in surveillance programs are more likely to be thoroughly evaluated beforehand, are more likely to be given a diagnosis of dysplasia or neoplasm even when asymptomatic and are more likely to comply with medical treatment, including maintenance anti-inflammatory medication. Comparisons of the rates of neoplasia or death between surveyed and nonsurveyed patients are, therefore, of questionable validity. Prophylactic colectomy, unlike surveillance colonoscopy, prevents death from colorectal cancer. Moreover, it is difficult to keep patients in surveillance programs, and those who withdraw from programs appear to be at high risk of developing cancer. Prophylactic colectomy should be strongly considered for patients with dysplasia, sclerosing cholangitis, longstanding pancolitis (especially if it began early in life) or a positive family history of colorectal cancer. This procedure is underused in clinical practice and is a good alternative to colonoscopic surveillance in high risk patients.